Recent Developments in the Evaluation of Information Retrieval Systems: Moving Towards Diversity and Practical Relevance - Mandl, T. (Informatica)
Recent Developments in the Evaluation of Information Retrieval Systems: Moving Towards Diversity and Practical Relevance